2020
DOI: 10.1021/acsomega.0c01510
|View full text |Cite
|
Sign up to set email alerts
|

The Active Center of Co–N–C Electrocatalysts for the Selective Reduction of CO2 to CO Using a Nafion-H Electrolyte in the Gas Phase

Abstract: To contribute a solution for the global warming problem, the selective electrochemical reduction of CO 2 to CO was studied in the gas phase using a [CO 2 (g), Co–N–C cathode | Nafion-H | Pt/C anode, H 2 /water] system without using carbonate solutions. The Co–N–C electrocatalysts were synthesized by partial pyrolysis of precursors in inert gas, which were prepared from various N-bidentate ligands, Co(NO 3 ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…Of course, the varying catalyst preparation and electrochemical test conditions also affect the observed catalytic activity for EOR but the performance and mechanism of Pt–Ru as a catalyst for EOR remain unclear. Utilization of the SPE electrolysis cell for H 2 production has many advantages over conventional electrolysis systems, for example, a lower terminal voltage, easy separation of the reactant from the electrolyte, and so on. …”
Section: Introductionmentioning
confidence: 99%
“…Of course, the varying catalyst preparation and electrochemical test conditions also affect the observed catalytic activity for EOR but the performance and mechanism of Pt–Ru as a catalyst for EOR remain unclear. Utilization of the SPE electrolysis cell for H 2 production has many advantages over conventional electrolysis systems, for example, a lower terminal voltage, easy separation of the reactant from the electrolyte, and so on. …”
Section: Introductionmentioning
confidence: 99%
“…in the S–Co–Ni/N–C- T catalysts, while S–Co/N–C-850 shifted by ∼0.18 eV (Co 2p3/2) and 0.19 eV (Co 2p3/2). 34,35 Homoplastically, the Ni 2p high-resolution XPS spectra in Fig. 5i show a shift to a lower B.E.…”
Section: Resultsmentioning
confidence: 96%
“…MEA CO 2 RR electrolyzers offer several advantages, compared with systems with flowing-electrolyte; therefore, recently researchers have developed electrolyte-free systems for efficient CO 2 RR. 32,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] It has been reported that MEA (or zero-gap or fuel cell-like) systems show a lower resistance and cell potential due to the absence of electrolytes. In addition, pumping an electrolyte brings some complexities to the systems (e.g., pumping, purification of electrolyte, etc.…”
Section: Recent Advances In Mea Systems For Co 2 Rrmentioning
confidence: 99%
“…Production of CO by using CO-selective Au and Ag electrocatalysts has been the main application of MEA systems for CO 2 RR. 42,45,46,[48][49][50][51][52][53]62,63 31 Using CEMs results in an acidic environment on the cathode side, causing a severe hydrogen evolution reaction (HER), thereby, they used an alkaline ion-exchange membrane. As can be seen in Figure 3B, CO 2 RR occurs on Au (as the CO-selective electrocatalyst), deposited on an alkaline polymer electrolyte membrane coupled with oxygen reduction in the anode (IrO 2 ) with pure water.…”
Section: Recent Advances In Mea Systems For Co 2 Rrmentioning
confidence: 99%